OP354 Cost-Effectiveness Analysis Of Different Prenatal Screening Strategies For Down Syndrome In China: Data From Shandong Province. (December 2020) - Du, Yanqiu; Shang, Wenru; Huang, Jiayan
Abstract : Introduction: There are large differences between the prenatal screening strategies for Down Syndrome (DS) in different provinces in China. In Henan province there is a serological triple screening in the second trimester (STS) strategy, while in Shandong province contingent non-invasive prenatal testing (NIPT) screening strategy (NIPT delivered to older pregnant women) is used, and there is a universal NIPT screening strategy in Anhui province. Moreover, many factors varied widely in different regions, such as the proportion of older pregnant woman and the ability of people to pay. This study aimed to determine the cost-effectiveness of current strategy in Shandong compared with strategies in other provinces. Methods: A decision tree model was developed according to the screening strategies in different provinces. Four screening strategies were involved, universal STS strategy, contingent STS strategy, contingent NIPT strategy, and universal NIPT strategy. Cost-effectiveness analysis was conducted from a societal perspective in a simulated cohort of 100, 000 pregnant women. The data of costs and epidemiologic parameters were collected from field surveys in Shangdong and a literature review. Results: The universal STS strategy, contingent STS strategy, contingent NIPT strategy, and universal NIPT strategy could prevent 17.0, 40.0, 46.2, and 53.6 DS births, respectively. There was no strategy dominated by others. The universal NIPT strategy and contingent NIPT strategy would decrease invasive procedures for prenatal diagnosis, resulting in fewer procedure-related miscarriages. The sensitivity analysis showed that the effectiveness of the screening strategy is significantly influenced by the resident's acceptance of NIPT. Conclusions: From the perspective of maximizing the effect, the universal NIPT strategy is the optimal strategy. But taking into account the resident's and government's ability to pay, contingent NIPT Strategy may be appropriate for the current situation in Shandong. To ensure a better cost-effective advantage in the universal NIPT strategy, the government should provide health education to increase the acceptance of NIPT while controlling the price of NIPT.